Pengaruh Motivasi Kerja, Gaya Kepemimpinan Dan Disiplin Kerja Terhadap Kinerja Di Kepengurusan Organisasi Ikatan Mahasiswa Lamongan (IKAMALA) – Malang Raya - Faizal Mubarok; Hadi Sunaryo; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to determine the effect of work motivation, leadership style and work discipline on performance, the sample of this research is the management of the IKAMALA organization. To collect data using a questionnaire, to analyze data using validity test, reliability test, normality test, multiple linear analysis, F statistic test and t statistic test, coefficient of determination test in IBM Social Sciences Statistical Package (SPSS) Version 16.0From the results of calculations with SPSS which is a variable of Work Motivation, Leadership Style and Work Discipline have a simultaneous and significant effect on purchasing decisions. While partially the variables of Work Motivation, Leadership Style and Work Discipline have a positive and significant effect on performance. Keywords: Work Motivation; Leadership Style; Work Discipline; Performance